Using Authentic Materials to Improve Paragraph Writing Skills in Senior High School - HB, Lukman; Said, Rosnaimah; Haidir, Haidir; Fitriani, Fitriani (Journal of English Culture, Language, Literature and Education, 2024)
The aim of the research was to determine whether or not authentic materials are attractive to SMA Negeri 9 Bulukumba students in the tenth grade, as well as to improve the students' achievement in paragraph writing utilising authentic resources. Quasi-experiment research methodology was used. The study was conducted in the academic year of 2023–2024 at SMA Negeri 9 Bulukumba. There were 300 students in the study, divided into 10 classes. Out of 300 students, 40 were chosen randomly and divided into two groups: the control group and the experimental group. This made up the sample. Test writing instruments were employed. The test was used to gather information about the students' writing proficiency. The t-test was used to evaluate the data. The study's findings demonstrated that students' proficiency in writing paragraphs with authentic materials is greater to their proficiency with writing paragraphs without them. The mean scores of the students’ post-test who were taught using authentic materials were 76.55. However, the students' achievement on the post-test that was taught without the use of authentic materials had a mean score of 59.75. It can be stated, then, that teaching students with actual materials improves their ability to write paragraphs.